Dragons are real! - Hatam, Holly (New York : Random House Children's Books, 2019)
Describes how dragons are made of moonlight, courage, and sparks.
On board pages.
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Board books; Board books; Board books